2013
DOI: 10.1371/journal.pone.0079800
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Engineering of Fungal GH5 and GH26 Beta-(1,4)-Mannanases toward Improvement of Enzyme Activity

Abstract: Microbial mannanases are biotechnologically important enzymes since they target the hydrolysis of hemicellulosic polysaccharides of softwood biomass into simple molecules like manno-oligosaccharides and mannose. In this study, we have implemented a strategy of molecular engineering in the yeast Yarrowia lipolytica to improve the specific activity of two fungal endo-mannanases, PaMan5A and PaMan26A, which belong to the glycoside hydrolase (GH) families GH5 and GH26, respectively. Following random mutagenesis an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(20 citation statements)
references
References 31 publications
0
19
0
1
Order By: Relevance
“…The rapid, sensitive, and substantial cost reduction in next‐generation sequencing has dramatically speeded up the development in sequence‐based metagenomics. Several mannanases, xylanases, cellulases, and esterases from fungi and bacteria , were isolated. GHs with bi‐ or multifunctional activities enhance the degradation of cellulose and hemicellulose biomass in bioethanol production .…”
Section: Discussionmentioning
confidence: 99%
“…The rapid, sensitive, and substantial cost reduction in next‐generation sequencing has dramatically speeded up the development in sequence‐based metagenomics. Several mannanases, xylanases, cellulases, and esterases from fungi and bacteria , were isolated. GHs with bi‐ or multifunctional activities enhance the degradation of cellulose and hemicellulose biomass in bioethanol production .…”
Section: Discussionmentioning
confidence: 99%
“…Studies in cellulolytic fungi revealed that linkers undergo modifications such as glycoslation and have also been shown to directly bind to the cellulose substrate (Beckham et al 2012;Payne et al 2013;Sammond et al 2012;Srisodsuk et al 1993). Point mutations in different fungal GH-CBM linkers have also been shown to significantly affect the activity of 506 the enzymes and their stability (Couturier et al 2013;Lu et al 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Hence, a directed evolution strategy was carried out to improve the catalytic efficiencies of PaMan5A and PaMan26A. It allowed the identification of hot-spots within the active site cleft of both mannanases (Couturier et al, 2013b). In particular, a mutant of PaMan26A with an increased activity exhibited two mutations, P140L and D416G.…”
Section: P Anserina Enzymes In Saccharification Assaysmentioning
confidence: 99%
“…The former was located in the linker between the catalytic domain and the CBM, the latter at the entrance of the catalytic cleft. It was hypothesized that the substitution of a proline by a leucine residue increased the flexibility, and thus resulted in an improved enzymatic activity, while the loss of the D416 side chain could facilitate the entrance of the substrate into the active site (Couturier et al, 2013b).…”
Section: P Anserina Enzymes In Saccharification Assaysmentioning
confidence: 99%